Pedological data for the study of soils developed over a limestone bed in a humid tropical environment - Ofem, Kokei Ikpi; John, Kingsley; Ediene, Victoria Francis; Kefas, Patrick Katan; Ede, Alungbe Moses; Ezeaku, Victor Ikemefuna; Pawlett, Mark (Springer, 2023)
Lithological characteristics interact with other factors of soil formation to define soil genesis. This becomes more interesting as data on the mineral and elemental oxide components of soils developed from limestone are rarely available in the humid tropical environment. The present study investigated the elemental oxide content, forms of sesquioxides, and clay mineral species in some limestone soils. Soil samples were obtained from three (3) crestal soil profile pits and analyzed for elemental content by the use of an X-ray fluorescence spectrometer, and sesquioxide forms by inductively coupled plasma–mass spectrometer. Analyses were done in triplicates. The mineralogy of the clay fraction was determined on the A, B, and C horizon samples using an X-ray diffraction technique. The occurrence of SiO2 (203–277 g/kg), Al2O3 (65–105 g/kg), and Fe2O3 (14–95 g/kg) in substantial amounts over MnO2, ZrO2, and TiO2 with negligible quantities of CaO suggested comparatively more developed soils in the Agoi Ibami and Mfamosing tropical rainforests. Crystalline form of Fe was dominant over amorphous form, with indications of the co-migration of dithionite Fe with clay to the B horizons of the soils. Quartz, kaolinite, montmorillonite, and chlorite-vermiculite-montmorillonite interlayered minerals dominated the clay mineralogy of the studied soils. Mineral transformation places the soils at the transitory stage from the intermediate to the complete stage of soil development. The expanding clay minerals are most likely to increase plant nutrient adsorption and soil fertility status to accommodate the cultivation of a wider range of crops.
Keywords: Soil genesis; Clay mineralogy; Forms of Fe and Al; Limestone